Fostering Entrepreneurship Among Millennials: A Systematic Literature Review Of Trends, Challenges, And Opportunities - Nissa Ghulma Ratnasari (Jurnal Impresi Indonesia, 2025)
Entrepreneurship has become a major driver of economic growth and innovation in the modern era. The millennial generation, which is the largest group in the workforce today, has great potential to become successful entrepreneurs. However, they also face unique challenges in starting and growing businesses. This study aims to conduct a systematic review of the literature on trends, challenges, and opportunities in fostering entrepreneurship among millennials. By analyzing the results of previous research, this study seeks to provide a better understanding of how to facilitate and support millennial entrepreneurship, as well as identify areas of advanced research needed to improve the success of millennial entrepreneurs. The initial search keyword series is "entrepreneurship", "entrepreneurial". Then, "millennials", "generation", "youth", are also included as additional search strings. The main objective of this study is to identify and map existing research on millennial entrepreneurship, including the journal sources used. This research has six specific objectives, namely (1) to examine and compile the terminology of research objectives on millennial generation entrepreneurship based on the thoughts of previous researchers, (2) to explain the context of the research conducted by researchers on the topic of millennial generation entrepreneurship, (3) to identify important variables that are the subject of study in previous studies related to millennial entrepreneurship, (4) to classify existing research about entrepreneurship of the millennial generation based on the research methods used. (5) elaborating the discussion of research results and conclusions relevant to the topic of entrepreneurship of the millennial generation, (6) identifying the limitations and practical implications of previous research to answer trends, challenges, and opportunities to fill research gaps that in the future can be a reference for further research on entrepreneurship of the millennial generation. This study emphasizes that entrepreneurship among millennials is a complex and multi-dimensional phenomenon, which is strongly influenced by a combination of personal factors such as individual values, self-efficacy, and expectations, social factors such as cultural norms and social networks, and contextual factors such as the education ecosystem, digital technology, and public policy.